Detection of anti-SARS-CoV-2 antibodies and its seroprevalence in Zavidovići municipality of Zenica-Doboj Canton, Bosnia and Herzegovina - Ibrahimagić, Amir; Huseinagić, Senad; Sarajlić-Spahić, Selvedina; Bašić, Fatima; Durmišević, Jasmin (International Journal of Health Sciences, 2022)
Objectives: Improved serological detection of specific antibodies against SARS-CoV-2 could help estimate the true number of infections. Methods: A total of 443 serum samples provided by unvaccinated patients of all ages with unknown COVID-19 status that were originally submitted for routine screening or clinical management from outpatient laboratory during the March – April 2021 (third wawe) were collected. Seroprevalence of IgM/IgG antibodies was determined by lateral flow immunoassay (Tigsun, Beijing, China). Results: Among 443 serum samples, 186 (42.0%) were positive (incidence of 5.2/1000) with slight predominace of females, 104 (55.9%), highest seropositivity in 25-50 and 51-64 years age groups, 61 (32.8%) and 57 (30.6%), respectively (p<0.05); rural population was more prevalent, 101 (54.3%) (p<0.05) and active workers, 86 (41.1%). Almost equal number of patients were with or without symptoms, 48.4% and 51.6%, respectively. For the comparison, in the same period it was registered 296 (out of 855; 34.6%) PCR SARS-CoV-19 positive persons (incidence of 8.2/1000) with the higher gender (females) and the higest age prevalence in 51-64 years age group (36.8%). In the period March 2020 – June 2021 it was registered 804 (out of 3323; 24.2%) (incidence of 22.3/1000) PCR SARS-CoV-19 positive persons with no significant gender and significant age difference (25-50 and 51-64 years group, respectively). Conclusion: In the regions with high prevalence/incidence of SARS-CoV-2 in the general population (Bosnia and Herzegovina is on the World top on the number of deaths) seroprevalence measuring can help tracking the spread of disease.